Research and curricular reform in dentistry undergraduate courses: origin challenges to current problems - Maltagliati, Luciana Ávila; Goldenberg, Paulete (Saúde e Sociedade, 2011)
The study aims to characterize the space of research in curricular organization and to identify curricular reform trends in Dentistry schools in the city of São Paulo. METHODS: from the analysis of documents and interviews with professionals who are responsible for the undergraduate courses of the investigated institutions, the study describes the development of the curricular structure and the institutionalization of research; characterizes the didactic program involving the instruction of scientific methodology; and identifies the trends and perspectives of change in curricular organization. RESULTS: valuing the space of research, as recommended by Brazil's Curricular Guidelines, the institutions provide scientific instruction in the Dentistry undergraduate program and students are stimulated to get involved with research projects in the scope of the scientific initiation program, in the extra-curricular space. These measures attest efforts of curricular revision, in view of the legal recommendations, without reaching, however, the structuring of the curriculum based on teaching through research.